2013
DOI: 10.1155/2013/789373
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Controlling the Oxide Reduction during Sintering of Chromium Prealloyed Steel

Abstract: Temperature intervals of oxide reduction processes during sintering of the Fe-3%Cr-0.5%Mo prealloyed powder using continuous monitoring of processing-exhaust gas composition (CO, CO2, and H2O) were identified and interpreted in relation to density (6.5–7.4 g/cm3), sintering temperature (1120 and 1200°C), heating and cooling rates (10 and 50°C/min), carbon addition (0.5/0.6/0.8%), type (10%H2-N2, N2), and purity (5.0 and 6.0) of the sintering atmosphere. The progress in reduction processes was evaluated by oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
(21 reference statements)
0
9
0
2
Order By: Relevance
“…Conversely, reduced ductility of Cr and Mn sintered steels has been associated, e.g. by Hryha et al [18] and Hrubovcakova et al [19], with bound-a) b) Fig. 17.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, reduced ductility of Cr and Mn sintered steels has been associated, e.g. by Hryha et al [18] and Hrubovcakova et al [19], with bound-a) b) Fig. 17.…”
Section: Discussionmentioning
confidence: 97%
“…After atomization, average oxygen content of as-atomized powder was found to be 2.09 wt.%. Pseudo-binary phase diagram of a Fe-3Cr-0.5Mo and H 2 O system showed that three kinds of oxides exist in the high temperature, low H 2 Figure 1 [21]. …”
Section: Atomized Powdersmentioning
confidence: 99%
“…Most iron powder is used in the production of high-strength steel components, which typically rely on alloying elements such as nickel (Ni), copper (Cu) and molybdenum (Mo) for their strength [1][2]. However, the high cost of these traditional alloying elements has created a need for cheap and efficient alternatives in order to reduce overall product costs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations